Neuroesthetics: Perspectives and reflections - Fogliano, Fernando L. [UNESP]; Oliveira, Hosana Celeste [UNESP] (My University, 2016)
This paper presents some considerations regarding the aesthetic experience from a neuroaesthetic point of view. The approach proposed here can take the discussions beyond the field of art allowing the aesthetic experience to be considered as a key aspect of subjectivity and interactions in the world. A reflection on the roles of emotion and language as fundamental aspects of the aesthetic experience is presented. Based on this reflection, some assumptions that are at the core of culture are made and re-framed here considering the postmodern turn.